The Relationship Between Family Support and Stress Levels in Diabetic Melitus Patients at the Pekauman Health Center, Banjarmasin - Elsi Nestriani, Ni Wayan; Tjomiadi, Cynthia Eka Fayuning; Manto, Onieqie Ayu Dhea (PROMOTOR, 2025)
Diabetes is chronic disease and has a significant impact on quality of life if not managed properly. Patients with diabetes mellitus often face psychological challenges such as stress related to the worries and burdens arising from the disease. Diabetes mellitus patients need support from their family as a support system to help them cope with the worries and emotional burden they feel. Analyzing the relationship of Family Support to Stress Levels in Diabetes Mellitus Patients at Pekauman Health Center Banjarmasin. Quantitative research type analytic survey cross sectional design. The sample was 48 DM patients at the Banjarmasin Pekauman Health Center. The research instrument used a questionnaire. Data were analyzed using the chi square test. There is a relationship between family support and stress levels in patients with diabetes mellitus at the pekauman health center in banjarmasin (p value 0.011). Family support for patients with diebates mellitus can reduce stress levels. Based on the results of the bivariate test in this study, the p value <0.05 is 0.011.